Identifying shared priorities for a bioregional approach to restoration in the Northern Gulf of Mexico - Guilbeau, Kelly G.; Hijuelos, Ann C.; Romañach, Stephanie S.; Steyer, Gregory D. (Frontiers in Ecology and Evolution, 2022)
Natural resource management is often challenged with a mismatch between the scale of decision-making and the scale of the biological, ecological, and physical processes that control a system. Bioregional approaches to adaptive management have emerged as an approach to inform natural resource management at ecologically relevant scales and across multi-level governance structures. The implementation of adaptive management requires the determination of ecological and social priorities that can inform a desired system state across multiple governing bodies. We use the Northern Gulf of Mexico, United States, as a case study for a bioregional approach to adaptive management and illustrate a method for developing objectives and management priorities across programs and jurisdictions. Through this synthesis, using qualitative coding methods to develop a shared vocabulary across the diverse dataset, we identified commonalities and differences in ecological and human community priorities across the five states which line the Northern Gulf of Mexico. Using these shared priorities, we conceptualize a network of priority-focused objectives as a starting point for further stakeholder engagement and effectively monitoring and evaluating progress across boundaries. This approach serves as a framework for cross-program adaptive management by illustrating a desired system state that reflects the shared priorities among decision-making authorities in this region and offering individual programs or projects a method to articulate their contributions to the broader set of shared priorities Gulf-wide. This method can be used by restoration managers in any region of the world to align project objectives within cross-jurisdictional boundaries and illustrate the value of a bioregional approach to restoration.